2019
DOI: 10.1001/jamanetworkopen.2019.9775
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cardiovascular Disease Risk Among Firefighters After the World Trade Center Disaster

Abstract: Key PointsQuestionIs World Trade Center exposure on and after September 11, 2001, associated with long-term cardiovascular disease risk in Fire Department of the City of New York firefighters?FindingsIn this cohort study of 9796 firefighters, age-adjusted incident rates of cardiovascular disease were higher for firefighters with greater World Trade Center exposure. Both acute World Trade Center as well as repeated exposure during 6 or more months at the World Trade Center site appeared to be associated with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 42 publications
3
38
0
Order By: Relevance
“…For cardiovascular mortality, these findings build on a recent study among male firefighters, which observed an increased long-term risk of cardiovascular disease. 50 Although the investigators did not observe PTSD to be a risk factor, they controlled for intermediate conditions between PTSD and cardiovascular disease, and our group of responders was more diverse, including women. It is possible that the unaffiliated responders included in our sample may contribute a different risk profile, and the availability of postdisaster programs to responders, such as routine health screenings, were varied by organization.…”
Section: Discussionmentioning
confidence: 87%
“…For cardiovascular mortality, these findings build on a recent study among male firefighters, which observed an increased long-term risk of cardiovascular disease. 50 Although the investigators did not observe PTSD to be a risk factor, they controlled for intermediate conditions between PTSD and cardiovascular disease, and our group of responders was more diverse, including women. It is possible that the unaffiliated responders included in our sample may contribute a different risk profile, and the availability of postdisaster programs to responders, such as routine health screenings, were varied by organization.…”
Section: Discussionmentioning
confidence: 87%
“…Increased risk of cardiovascular disease (CVD) has been linked to airborne particulate exposures [ 136 ] and severe psychological stress [ 136 , 137 , 138 , 139 ]; therefore, WTC exposures and experiences may potentially increase CVD risks. The relationship between WTC exposures and CVD has been examined in several studies [ 54 , 76 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 ]. Registry enrollees were studied most often [ 54 , 141 , 143 , 144 , 145 , 146 , 147 ].…”
Section: Research Portfoliomentioning
confidence: 99%
“…In a recent cohort study of responding male firefighters ( n = 9796), age-adjusted incident rates of CVD (defined as myocardial infarction, stroke, unstable angina, coronary artery surgery or angioplasty, or CVD death from electronic medical records) were higher among firefighters with greater WTC exposure (HR = 1.44, 95% Cl: 1.09, 1.90), while controlling for other risk factors [ 140 ]. Excess risk of myocardial infarction (HR = 2.22, 95% CI: 1.30–3.82) and stroke (HR = 2.51, 95% CI: 1.39, 4.47) was evident in a prospective study of general responders with PTSD compared to those without, in multivariable models adjusting for age, gender, body mass index (BMI), blood pressure, smoking, respirator use, and total cholesterol [ 142 ].…”
Section: Research Portfoliomentioning
confidence: 99%
See 1 more Smart Citation
“…Some survivors also witnessed traumatic events such as seeing airplanes strike the towers. These exposures led to the development of a variety of physical and mental conditions, such as asthma [ 1 , 2 , 3 , 4 , 5 ], post-traumatic stress disorder (PTSD) [ 6 , 7 , 8 , 9 ], heart disease [ 6 , 10 , 11 ], stroke [ 8 ], and cancer [ 12 , 13 ]. Some of these diseases appeared in survivors in the first several years after the attacks (e.g., asthma, PTSD), while other diseases have longer latency periods and have appeared 10–15 years after the 9/11 attacks (e.g., heart disease, stroke, certain cancers).…”
Section: Introductionmentioning
confidence: 99%